Neuromuscular Junction Protection for the Potential Treatment of Amyotrophic Lateral Sclerosis. (7th August 2012) - Krakora, Dan; Macrander, Corey; Suzuki, Masatoshi
Abstract : Amyotrophic lateral sclerosis (ALS) is a neuromuscular disease characterized by the progressive degeneration of upper and lower motor neurons (MNs), leading to muscular atrophy and eventual respiratory failure. ALS research has primarily focused on mechanisms regarding MN cell death; however, degenerative processes in the skeletal muscle, particularly involving neuromuscular junctions (NMJs), are observed in the early stages of and throughout disease progression. According to the "dying-back" hypothesis, NMJ degeneration may not only precede, but actively cause upper and lower MN loss. The importance of NMJ pathology has relatively received little attention in ALS, possibly because compensatory mechanisms mask NMJ loss for prolonged periods. Many mechanisms explaining NMJ degeneration have been proposed such as the disruption of anterograde/retrograde axonal transport, irregular cellular metabolism, and changes in muscle gene and protein expression. Neurotrophic factors, which are known to have neuroprotective and regenerative properties, have been intensely investigated for their therapeutic potential in both the preclinical and clinical setting. Additional research should focus on the potential of preserving NMJs in order to delay or prevent disease progression